👤
Theozeciu40
a fost răspuns

3. Så se efectueze: a) 5sqrt(3) * (2sqrt(2) + sqrt(12)) - sqrt(6) = c) sqrt(2) * (3sqrt(2) + sqrt(3)) - 2sqrt(3) * (5sqrt(2) + 4sqrt(3)) = c 14sqrt(6) - 2sqrt(3) * (sqrt(2) + sqrt(3)) + 3sqrt(2) * (1 + sqrt(2)) = 3) [4sqrt(5) * (sqrt(2) - sqrt(3)) - sqrt(10) + 3sqrt(15)] * 2sqrt(2) = b 5sqrt(5) * (3sqrt(5) + sqrt(2)) + sqrt(2) * (2sqrt(8) + sqrt(5)) = 4 3sqrt(11) * (sqrt(7) - 4sqrt(11)) + 3sqrt(7) * (sqrt(11) - sqrt(7)) = 0.3sqrt(2) - 2sqrt(5) * (1 - sqrt(2)) - 2sqrt(10) + sqrt(2) = b) [(- 2sqrt(3))(2 - sqrt(2)) + (- 3sqrt(6))](- sqrt(2)) = h​

3 Så Se Efectueze A 5sqrt3 2sqrt2 Sqrt12 Sqrt6 C Sqrt2 3sqrt2 Sqrt3 2sqrt3 5sqrt2 4sqrt3 C 14sqrt6 2sqrt3 Sqrt2 Sqrt3 3sqrt2 1 Sqrt2 3 4sqrt5 Sqrt2 Sqrt3 Sqrt10 class=